Variation of calcium, copper and iron levels in serum, bile and stone samples of patients having different types of gallstone: A comparative study - Khan, Mustafa (2017)
Background Epidemiological data among the human population has shown a significantly increased incidence of gallstone (GS) disease worldwide. It was studied that some essential (calcium) and transition elements (iron and copper) in bile play an important role in the development of GS. Method The estimation of calcium, copper and iron were carried out in the serum, gall bladder bile and different types of GS (cholesterol, mixed and pigmented) of 172 patients, age ranged 20–55 years. For comparative purpose age matched referents not suffering from GS diseases were also selected. Biliary concentrations of calcium (Ca), iron (Fe) and copper (Cu) were correlated with their concentrations in serum and different types of GS samples. The ratio of Ca, Fe and Cu in bile with serum was also calculated. Understudy metals were determined by flame atomic absorption spectroscopy after acid decomposition of matrices of selected samples. Results The Ca concentrations in serum samples were significantly higher in patients with pigmented GS as compared to controls (p < 0.005), whereas for patients having cholesterol and mixed GS the concentrations were on the lower side. Biliary Ca concentrations of patients were found to be higher than controls, but difference was significant for pigmented GS patients (p > 0.001). The contents of Cu and Fe in serum and bile of all patients (except female cholesterol GS patient have low serum iron concentration) were found to be higher than control, but difference was significant in those patients who have pigmented GS. The concentration of Ca, Fe and Cu in different types GS were found in the order, Pigmented > mixed > cholesterol. The bile/serum ratio for Ca, Cu and Fe was found to be significantly higher in pigmented GS patients. Gall bladder bile was slightly alkaline in patients as compared to referents. The density of bile was found to be higher in patients as compared to the referents. Various functional groups present in different types of GS samples were confirmed by Fourier transform infra-red spectroscopy. Conclusion The higher density and pH of bile, elevated concentrations of transition elements in all types of biological samples (serum, bile and GS), could be an important factor for the formation of different types of GS.